International experiences with reduction of greenhouse gasses from dairy farms: strategy and implementation: U.S. - McMahan, Joe (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
"International experiences with reduction of greenhouse gasses from dairy farms: strategy and implementation: U.S." was presented by Joe McMahan at the Kick-off meeting on "Piloting and scaling of low emission development options in large scale dairy farms in China" on September 28th, 2020.